Assessment of irrigation water quality of Bogra District in Bangladesh (Bangladesh Journal of Agricultural Research, 2010)
Some important physio-chemical parameters of surface and groundwater of Bogra District were evaluated for the criteria of irrigation water quality. Forty four water samples were collected in the peak dry season (December-April) from different areas of Bogra District. The study revealed that temperature, pH, electrical conductivity (EC), total dissolved solids (TDS), sodium adsorption ratio (SAR), soluble sodium percentage (SSP), residual sodium carbonate (RSC), total hardness (Ht) and Kelly’s ratio of waters were found within the permissible limits for irrigation purposes. Any initiative for surface and groundwater development for planned irrigation practices is highly encouraged. Key Words: Irrigation water (surface and groundwater); quality; Bogra District. DOI: 10.3329/bjar.v34i4.5836Bangladesh J. Agril. Res. 34(4) : 597-608, December 2009